IMPLICATIONS OF THE AMENDMENT OF THE 1945 CONSTITUTION ON THE PRESIDENT'S PREROGATIVE RIGHTS IN THE JUDICAL SECTOR: President’s Prerogatif - Salisa (Jurnal Analisis Hukum, 2021)
Abstract The purpose of this research is to knowing of regulation and implementation of president Prerogatif before and after the amendment to the 1945 constitution as well as the implementation of the Prerogatif of the president in the judiciary in administering judicial power in Indonesia. Amendments to the 1945 constitution including the first amendment on October 19, 1999, the second amendment on August 18, 2000, the third amendment on November 9, 2001, and the fourth amendmenton August 10, 2002. President’s Prerogatif is a right that is owned by a head of state or head of government without any intervention from any party in exercising that right. The judicial field is a part of the judiciary, namely the state institution in charge of overseeing the passage of laws and regulations. The problem is how regulation and implementation of president prerogatif before and after the amendment to the 1945 constitution and how the implementation of the president’s prerogatif in the judiciary in exercising judicial power in Indonesia. The method used in writing this scientific paper is a normatif juridical method that is reviewing the laws and regulations and library books as well as accessing the legal journals relating to the problem. The result and discussion obtained show that there are differences in the implementation of the president’s prerogatif before and after the amendment to the 1945 constitution. The implementation of the president’s prerogatif in the judiciary is not a form of interference, but the implementation of the check and balance system in Indonesia.